Mastering ARKit : Apple's augmented reality app development platform - Nhan, Jayven (Apress, 2022)
Embark on a journey to build an augmented reality world. This book puts theory into practical application by building unique augmented reality apps specific to each chapter's topic. You'll learn to engineer successful, well-designed, and comprehensive augmented reality applications for Apple devices. First, uncover the foundation of augmented reality on Apple platforms. Understand the building blocks and inner workings of the technologies that power augmented reality. Then, learn about building AR apps using ARKit, SceneKit, SpriteKit, RealityKit, and RealityComposer. You'll study augmented reality app business models, designs, and content for the ultimate user experience. Plus, you'll cover the theories and practicalities of ARKit APIs such as surface detection, working with world maps, body motion capture, face tracking, object scanning and detecting, people occlusion, and more. Chapter by chapter, this book helps you to become an advanced augmented reality engineer. By the end of the book, you'll have the necessary mental models and tools to engineer delightful experiences in Apple's augmented reality platforms. What You'll Learn Build AR apps with SceneKit, SpriteKit, RealityKit, and RealityComposer Understand the business models that support augmented reality Incorporate surface detection, computer vision, and body motion capture in your apps Who This Book Is For iOS developers who want to expand their knowledge of ARKit. They should have a solid foundation in the Swift programming language and understand the basics of navigating Xcode.